2021
DOI: 10.1108/ijem-02-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and social intelligence assessment model for student character reinforcement

Abstract: PurposeThe purpose of this study is to help teachers resolve the difficulties in assessing the students' characters through the development of valid, reliable, goodness-of-fit statistic instrument of emotional and social intelligence assessment for elementary school students.Design/methodology/approachThis study used a research and development model from Plomp with five phases, such as investigation, design, realization, testing and implementation. The research subjects were 345 students of class IV amongst 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 27 publications
(34 reference statements)
0
9
0
1
Order By: Relevance
“…These competencies require special training for enhancement (Bonesso et al, 2020). Various ESI models are used to understand personal abilities and social skills of a person (Khilmiyah & Wiyono, 2021). These social skills or social intelligence also enhances commitment and learning in an individual specially in job sectors (Torabi, 2021;Mohadesi, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These competencies require special training for enhancement (Bonesso et al, 2020). Various ESI models are used to understand personal abilities and social skills of a person (Khilmiyah & Wiyono, 2021). These social skills or social intelligence also enhances commitment and learning in an individual specially in job sectors (Torabi, 2021;Mohadesi, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main task of the teacher is to educate students to have the ability to build the life and have the ability to solve the problems that will be faced in the future. Thus, the task of the teacher, in addition to providing knowledge, must also be able to develop students' emotional and social intelligence, which includes intrapersonal and interpersonal skills (Khilmiyah & Wiyono, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Endalan et al (2019) revealed that the main elements of abilities that are important for a child to have, related to emotional intelligence are: self-awareness or being able to recognize oneself; personal decision making; managing feelings; dealing with stress; empathy, and good communication; and open up. Indicators of emotional intelligence, according to Khilmiyah and Wiyono (2021), are as follows: being able to recognize one's own feelings; being able to respect one's own feelings; being able to manage their own feelings; being able to control one's own feelings; being able to feel the reality of one's own spirituality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations